2016
DOI: 10.1016/j.ceramint.2016.05.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthesis atmosphere on the proton conductivity of Y-doped barium zirconate solid electrolytes

Abstract: a b s t r a c tYttrium-doped barium zirconate ceramic powders were synthesized by the oxidant peroxide method in air and under controlled atmosphere of nitrogen inside a glove box. The powders were characterized by thermogravimetry, X-ray diffraction, scanning electron microscopy and transmission electron microscopy. After uniaxial cold isostatic pressing, green pellets were sintered at 1600°C for 4 h. The electrical conductivity behavior was accessed by electrochemical impedance spectroscopy. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…43 The quantitative difference at higher temperature may be due to anharmonic effects, which are not considered in the present work. The difference between the ground state value of D f G BaZrO 3 and that for 300 K is À1.34 eV, which is in good agreement with the experimental values of À1.33 eV and À1.19 eV at 300 K. 43,44…”
Section: Gibbs Free Energy Of Formation Of Bzo Bao and Zrosupporting
confidence: 87%
“…43 The quantitative difference at higher temperature may be due to anharmonic effects, which are not considered in the present work. The difference between the ground state value of D f G BaZrO 3 and that for 300 K is À1.34 eV, which is in good agreement with the experimental values of À1.33 eV and À1.19 eV at 300 K. 43,44…”
Section: Gibbs Free Energy Of Formation Of Bzo Bao and Zrosupporting
confidence: 87%
“…Previous impedance spectroscopy and calorimetric studies on BZY x were performed on samples prepared by the OPM synthesis method in a controlled N 2 atmosphere. The results showed that the conductivity is maximum when lower density and cleaner grain boundaries are present in the microstructure; the dopant is still in a dilute regime in the BZ matrix, which occurs for Y concentrations up to 20%, and the temperature of the measurement is high enough to allow enhanced mobility of the charge carriers. , In the present work, despite the higher water uptake at a lower temperature, protons will preferably occupy trapping sites, which makes them mostly unavailable for the conduction process. , …”
Section: Resultsmentioning
confidence: 59%
“…The results showed that the conductivity is maximum when lower density and cleaner grain boundaries are present in the microstructure; the dopant is still in a dilute regime in the BZ matrix, which occurs for Y concentrations up to 20%, and the temperature of the measurement is high enough to allow enhanced mobility of the charge carriers. 22,26 In the present work, despite the higher water uptake at a lower temperature, protons will preferably occupy trapping sites, which makes them mostly unavailable for the conduction process. 21,22 Figure 5 shows the Arrhenius plot of the equilibrium constant (4) of the reaction of proton incorporation (2).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The hydrogentested cells withstood the test condition with little to no degradation. The slight decrease in the V-T curve towards the latter half of the 700 ℃ could be due to agglomeration of the anode cermet exacerbated at higher temperatures (25,30). Cells tested with NM and SRM experienced much greater rates of performance degradation.…”
Section: Resultsmentioning
confidence: 99%